2013
DOI: 10.1177/1076029613498817
|View full text |Cite
|
Sign up to set email alerts
|

New Protocol for Detection of Intron 22 Inversion Mutation From Cases With Hemophilia A

Abstract: Conventional long PCR and I-PCR methods are work intensive, prolonged, and sometimes difficult to be standardize. The cDNA method is short, involves 3 short-segment amplifications, and is easy to reproduce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…However, quantitative reverse transcription PCR without gel electrophoresis cannot be used to diagnose Inv22 carriers. 18 Gau et al reported a method that used a different set of primers to amplify an intact exon 22 to 23 splice site PCR product 23 ; a potential drawback to using this method is that lack of an exon 22 to 23 diagnostic band could also be caused by improper PCR conditions or other experimental artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, quantitative reverse transcription PCR without gel electrophoresis cannot be used to diagnose Inv22 carriers. 18 Gau et al reported a method that used a different set of primers to amplify an intact exon 22 to 23 splice site PCR product 23 ; a potential drawback to using this method is that lack of an exon 22 to 23 diagnostic band could also be caused by improper PCR conditions or other experimental artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-based methods to detect Inv22 and Inv1 mutations 10,17 have been used in research and have also been proposed for clinical genotyping of HA patients. 18 These methods have been based on the presence or absence of PCR-amplified complementary DNA products spanning the normal exon 22 to 23 or exon 1 to 2 splice site, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of sequence FVIII gene by Gitschier et al (14) at Genetech in 1984, numerous mutations causing HA have been identified. The most common is the inversion of intron 22, which occurs in 40-50% of patients with severe HA (15), whereas the inversion of intron 1 is present in just 1-5% of patients (16).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mutation detection allows for carrier and prenatal diagnosis to be conducted [5].The intron 22 inversion (inv22) was first detected by means of a Southern blot assay [2]. This technique proves to be accurate, but has the disadvantage of being time-consuming and labour intensive [6]. The availability of Southern blot reagents has also become a major obstacle.…”
mentioning
confidence: 99%
“…Newer methods such as long-distance polymerase chain reaction (LD-PCR) and inverse PCR (I-PCR) have been described to detect the inversion [7,8]. However, LD-PCR is reportedly difficult to standardize and is sensitive to reductions in DNA quality [6,9]. I-PCR involves three steps including restriction, self-ligation and standard PCR analysis.…”
mentioning
confidence: 99%